EVALUATION OF THE DEVELOPMENT AND CORROSION RESPONSE OF ZA-27/PERIWINKLE SHELL COMPOSITE EXPOSED TO 0.5M HCl - Bala, Muhammad Nura; Abdullahi, Ibrahim; Yaro, Shuaibu Audu; Janga, Abubakar Alhaji; Chindo, Yusuf Mohammed (FUDMA Journal of Sciences, 2026)
Materials science and engineering designs materials tailored for specific needs by manipulating the relationships between processing, structure, and performance. Zinc-based ZA-27 alloys are prized for high strength but suffer a decrease in properties at temperatures above 80°C. This research aimed to develop a metal matrix composite using ZA-27 as the matrix and periwinkle shell ash as a low-cost reinforcement. Composites were produced via green sand casting using varying percentages (2%, 4%, 6%, 8% and 10%) of periwinkle shell ash as reinforcement. and particle sizes (+45 µm, +53 µm, and +63 µm). Three different test samples were produced, and corrosion was evaluated at room temperature in 0.5M HCl over 240 hours (10 days) using the weight-loss technique at time interval of 48 hours. Results showed that the unreinforced ZA-27 alloy exhibited better corrosion resistance than all reinforced composites. However, within the reinforced group, samples with +45 µm particle size and 10% ash content showed the highest relative resistance compared to +53 µm, and +63 µm. Corrosion rates for all samples decreased as exposure time increased due to the formation of a passive layer. It was also established that increased percentage reinforcement resulted to increased corrosion resistance.
Keywords: ZA-27 alloy, periwinkle shell ash, metal matrix composite, weight loss analysis, hydraulic acid, corrrosion